The Value of Total antioxidant Status and Serum Tumor Necrosis Factor-α Levels at 24–28 Weeks of Gestation in the Prediction of Optimal Treatment Protocol in Gestational Diabetes Mellitus - Ozler, S.; Oztas, E.; Uygur, D.; Ersoy, A. O.; Ergin, M.; Koca, C.; Danisman, N.; Erkaya, S. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aim: The aim of this study was to investigate the serum oxidative stress markers, antioxidant enzyme and tumor necrosis factor-α (TNF-α) levels at 24–28 weeks of gestation and to evaluate the predictive value of them on the subsequent treatment protocol in gestational diabetes mellitus (GDM).Methods: A total of 58 GDM patients (30 treated with only conventional healthy dietary recommendation (CHDR), 28 treated with insulin) and 30 healthy pregnant women at 24–28 weeks of gestation, were enrolled in this prospective case-control study. The oxidative status, antioxidant enzyme and TNF-α levels were evaluated to determine if there is an association with the need of insulin therapy for glycemic control by using multivariable logistic regression analysis.Results: TNF-α (OR=11.976, 95%CI: 2.441–58.754, P=0.002) and total antioxidant status (TAS) (OR=12.769, 95%CI: 2.464–66.182, P=0.002) were found to be predictive for GDM at 24–28 weeks of gestation. Besides, further evaluation considering the treatment modality showed that increased TNF-α (OR=18.615, 95%CI: 2.338–148.240, P=0.006) and lower TAS levels (OR=99.471, 95%CI: 2.865–3 453.061, P=0.011) were independent predictors of the need for insulin treatment in GDM patients.Conclusions: Increased TNF-α levels and low TAS are significantly associated with the increased risk of insulin requirement for achieving good glycemic control in GDM.
Keywords: gestational diabetes mellitus; insulin requirement; oxidative stress; tumor necrosis factor-α